Cloning, expression, purification and preliminary X‐ray diffraction studies of a novel AB5 toxin. Issue 8 (31st July 2013) - Ng, Natasha; Littler, Dene; Le Nours, Jérôme; Paton, Adrienne W.; Paton, James C.; Rossjohn, Jamie; Beddoe, Travis
<x xml:space="preserve">Abstract</x> AB5 toxins are key virulence factors found in a range of pathogenic bacteria. AB5 toxins consist of two components: a pentameric B subunit that targets eukaryotic cells by binding to glycans located on the cell surface and a catalytic A subunit that disrupts host cellular function following internalization. To date, the A subunits of AB5 toxins either have RNA‐N‐glycosidase, ADP‐ribosyltransferase or serine protease activity. However, it has been suggested that a novel AB5 toxin produced by clinical isolates of Escherichia coli and Citrobacter freundii has an A subunit with metalloproteinase activity. Here, the expression, purification and crystallization of this novel AB5 toxin from E. coli (EcxAB) and the collection of X‐ray data to 1.9 Å resolution are reported.